2020
DOI: 10.1257/aer.20181478
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing Education: Experimental Evidence from Liberia

Abstract: In 2016, the Liberian government delegated management of 93 randomly selected public schools to private providers. Providers received US$50 per pupil, on top of US$50 per pupil annual expenditure in control schools. After one academic year, students in outsourced schools scored 0.18 σ higher in English and mathematics. We do not find heterogeneity in learning gains or enrollment by student characteristics, but there is significant heterogeneity across providers. While outsourcing appears to be a cost-effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…For example, trials in Kenya and Liberia have shown in headtohead comparisons that the same programmes are less effective when put in the hands of government compared with private providers. 153,154 A metaanalysis of trials evaluating a wide range of health, education and social assistance interventions finds that those implemented by government are on average less effective than nonstate providers. 155 These studies typically focus on notforprofit organisations and less evidence exists for the value of contracting forprofit providers, whose involvement remains controversial.…”
Section: Government As a Project Of Shared Responsibility To Childrenmentioning
confidence: 99%
“…For example, trials in Kenya and Liberia have shown in headtohead comparisons that the same programmes are less effective when put in the hands of government compared with private providers. 153,154 A metaanalysis of trials evaluating a wide range of health, education and social assistance interventions finds that those implemented by government are on average less effective than nonstate providers. 155 These studies typically focus on notforprofit organisations and less evidence exists for the value of contracting forprofit providers, whose involvement remains controversial.…”
Section: Government As a Project Of Shared Responsibility To Childrenmentioning
confidence: 99%
“…An average of school-based testing (for students in school) and home-based tracking (for students out of school), combined with classroom observations, as part of a randomised controlled trial in Liberia, cost US$150 per child. 36 37 …”
Section: Practical Lessons For Phone-based Assessmentsmentioning
confidence: 99%
“…This focus informed the design of all teaching and learning materials, from textbooks to teacher handbooks and lesson plans. These materials also incorporated scripted lessons, which have been shown to work in numerous settings (Piper et al 2018;Romero, Sandefur, and Sandholtz 2020;Eble et al 2021) and are alleged to be particularly helpful for teachers with less training and suboptimal supervision, potentially raising the level of the "floor" of teaching quality in challenging contexts. The absence of heterogeneity in the treatment effect shows the intervention worked similarly for all children.…”
Section: Features Uniqueness and Scalability Of The Interventionmentioning
confidence: 99%